Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1093/occmed/47.5.301
|View full text |Cite
|
Sign up to set email alerts
|

The problems associated with pesticide use by irrigation workers in Ghana

Abstract: The use of pesticides in Ghanaian agriculture, though beneficial in reducing crop loss both before and after harvest, has been associated with threats to human health often due to the misapplication of the chemicals. This study was an initial attempt to explore the knowledge, attitudes and practices of 123 farm workers on three irrigation project areas in the Accra Plains, Ghana, regarding the safe handling and use of pesticides, to assess the prevalence of symptoms associated with organophosphorus pesticides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
79
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(107 citation statements)
references
References 1 publication
15
79
2
3
Order By: Relevance
“…DDT and dieldrin have been used in agriculture and public health (malaria eradication) (Clarke et al, 1997) while aldrin have been used against termites with lindane and endosulfan restricted for the control of capsids on cocoa, stem borers in maize and pest on coffee. As compared to DDE, DDT, and endosulfan sulphate, the concentrations of HCHs (γ-HCH and δ-HCH) were lower, because they are much less bioaccumulative with low lipophilicity and short half-life in biota (Sudaryanto et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…DDT and dieldrin have been used in agriculture and public health (malaria eradication) (Clarke et al, 1997) while aldrin have been used against termites with lindane and endosulfan restricted for the control of capsids on cocoa, stem borers in maize and pest on coffee. As compared to DDE, DDT, and endosulfan sulphate, the concentrations of HCHs (γ-HCH and δ-HCH) were lower, because they are much less bioaccumulative with low lipophilicity and short half-life in biota (Sudaryanto et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…These practices are not governed by strict regulations concerning the training and education of farmers. As information from the questionnaire and previous work (Clarke et al 1997;Ntow et al 2006) revealed that farmers' handling and storage of chemical pesticides, personal hygiene, and the proper use of personal protective equipment in Ghana is below a reasonable standard, it is unexpected that the biological exposure marker failed to demonstrate an equivalent result.…”
Section: Discussionmentioning
confidence: 99%
“…The studies pointed out that majority of the samples contaminated by chlorinated pesticides exceeded the maximum limits which could cause pesticide hazard to the consumer [30,31]. It was observed that organochlorines persisted in the environment long after being banned and may be involved in the causation of breast cancer as a result of estrogenic activity [32]. Alkene, alkyne, esters, acids, phenols and pyrethrum were found in small quantity in all the food samples taken in all sampled markets.…”
mentioning
confidence: 99%